(untitled) (International Journal of Innovative Technologies in Economy, 2021)
Venture capital is a way of financing generally used to support companies and small- business enterprises and innovative enterprises. It is becoming a very popular source of capital for new companies or enterprises that do not have access to capital markets, bank loans or other credit instruments. Venture capital provides financing during the various stages of the company’s life cycle. For the small and medium sector, venture capital financing is one of the most accessible and efficient.